Thermoelectric transport and Hall measurements of low defect Sb 2Te3 thin films grown by atomic layer deposition - Zastrow, S.; Gooth, J.; Boehnert, T.; Heiderich, S.; Toellner, W.; Heimann, S.; Schulz, Stephan; Nielsch, Kornelius (Semiconductor Science and Technology, 2013)
Sb2Te3 has recently been an object of intensive research since its promising applicability in thermoelectric, in phase-change memory devices and as a topological insulator. In this work, we report highly textured Sb2Te3 thin films, grown by atomic layer deposition on Si/SiO2 wafers based on the reaction of SbCl 3 and (Et3Si)2Te. The low deposition temperature at 80 °C allows the pre-patterning of the Sb2Te 3 by standard lithography processes. A platform to characterize the Seebeck coefficient S, the electrical conductivity σ as well as the Hall coefficient RH on the same film has been developed. Comparing all temperature-dependent transport properties, three different conductive regions in the temperature range of 50-400 K are found. Room temperature values of S = 146 × 10-6 VK-1, σ = 104 Sm -1 and mobility M = 270.5 × 10-4 m2 V-1 s-1 are determined. The low carrier concentration in the range of n = 2.4 × 1018 cm-3 at 300 K quantifies the low defect content of the Sb2Te3 thin films. © 2013 IOP Publishing Ltd.
CRIS-Team Scopus Importer:2023-03-20